Sie sind auf Seite 1von 2

1.)

2.)

y + 3x = - 12

 

x = - 3y + 16 2x - 3y = - 4

y

= - x - 4

3.)

y = 4x - 14

4.)

x = - 5y + 16

 

y

+ 2x = 22

x

= 5y - 4

5.)

6.)

3y + 3x = 0

 

y = - 3x + 32 4y + 2x = 28

y

= 3x - 32

7.)

x = 3y - 19 4x + 4y = 4

8.)

x = - 4y - 23 4x + y = 28

9.)

x = 4y + 18

10.)

5x = - 3y - 25

 

x

+ 2y = - 24

x

= - 3y - 17

11.)

y = 5x + 7

12.)

- 5y + x = 44

 

y

+ 2x = - 7

y

= - 4x + 8

13.)

2x = - 5y - 19

14.)

 

x = - y + 1

 

x = 3y - 25 - 3x + y = 27

1 of 2

PDF created with pdfFactory trial version www.pdffactory.com

6/7/2009 8:09 AM

15.)

x = 3y - 3

16.)

x = 2y - 13

x

- 2y = -1

x

+ 2y = 15

17.)

- y - 5x = 9

18.)

y

= x + 9

x = - 4y - 15 3x + 5y = - 17

19.)

4x = - 3y + 0

20.)

x = 5y - 38

x

= - y - 1

x

+ 3y = 26

21.)

x = 3y + 3

22.)

- 5x = 3y - 28

x

- 4y = 3

x

= - y + 6

23.)

4y + x = - 9

24.)

5x = - 3y + 53

y

= - 5x + 12

x

= - y + 11

25.)

- 4y - 2x = - 6

y = - 4x + 12

2 of 2

PDF created with pdfFactory trial version www.pdffactory.com

6/7/2009 8:09 AM